2022
DOI: 10.1088/1475-7516/2022/04/014
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational radiation from a binary system in odd-dimensional spacetime

Abstract: We explore possible manifestations of an odd number of extra dimensions in gravitational radiation, which are associated with violation of Huygens' principle in flat odd-dimensional spacetime. Our setup can be regarded as the limit of an infinite compactification radius in ADD model and is not viable as realistic cosmology, but it still may be useful as a simple analytically solvable model catching certain features of more realistic scenarios. The model consists of two point masses moving inside a flat three-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…However, being based on the computations in the momentum space, which are irrelevant to the dimensionality of the spacetime, it does not provide us with the information about the structure of radiation field in the wave zone and the role of tail term in the formation of radiation. Recently, it has been shown that the role of tail term in the radiation can be studied in two ways: by Fourier transforming retarded Green's functions over the time coordinate [50] or by modifying the radiation definition [17,32,74,75]. In this paper, we follow the second approach.…”
Section: Jcap10(2023)019mentioning
confidence: 99%
See 3 more Smart Citations
“…However, being based on the computations in the momentum space, which are irrelevant to the dimensionality of the spacetime, it does not provide us with the information about the structure of radiation field in the wave zone and the role of tail term in the formation of radiation. Recently, it has been shown that the role of tail term in the radiation can be studied in two ways: by Fourier transforming retarded Green's functions over the time coordinate [50] or by modifying the radiation definition [17,32,74,75]. In this paper, we follow the second approach.…”
Section: Jcap10(2023)019mentioning
confidence: 99%
“…(2.19). Also, the emitted part of the field (2.31) is given by the integral over the history of particle motion preceding the retarded time τ ≤ τ , which is a characteristic feature for all odd dimensions [17,32,74]. It is these integrals over the history of source motion that should result…”
Section: Jcap10(2023)019mentioning
confidence: 99%
See 2 more Smart Citations
“…However, these black holes carry tidal charges, which can take negative values, unlike the electric charge of Reissner-Nordström black holes. 1 The observational consequences of tidal-charged black holes have been discussed in the literature in the context of black hole shadow and gravitational wave observations [46][47][48][49][50][51][52][53][54][55][56][57][58]. In the present context, we consider the effect of tidal charge on the EMRI waveform and check whether LISA observation can put a tighter constraint on this parameter and, consequently, on the extra dimensions.…”
Section: Introductionmentioning
confidence: 95%